2019
DOI: 10.20546/ijcmas.2019.811.150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Nutrient Management on Growth and Flowering of African Marigold (Tagetes erecta) cv. Pusa Narangi Gainda

Abstract: Marigold, a member of the family Asteraceae, is native to Central and South America especially Mexico (Kaplan, 1960). Cultivated genera include Tagetes erecta and Tagetes patula, commonly referred to as African marigold and French marigold, respectively. African marigold is one of the most important loose flower crops grown commercially in many parts of the country. Flowers of marigold are used in garland-making, wreaths, as religious offering, in hall decoration, etc. It is in great demand as loose flower thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…Biofertilizers are microbial inoculants which are capable in nitrogen fixation, phosphorus solubilising and decomposing organic matter at a faster rate and thus help in improving the soil fertility and boosting crop productivity. These results confirm the findings of Sharma et al, (2017) [13] , Tiwari et al, (2018) [17] and Kumura et al, (2019) [7] in African marigold. The maximum plant spread (21.80, 27.83 and 34.94 cm 2 ) at 30, 60 and 90 days after transplanting was recorded with T7 -75% RDF + FYM + VC + Biofertilizers, followed by treatment T6-75% RDF + VC + Biofertilizers.…”
Section: Effect Of Different Organic and Inorganic Sources Of Nutrien...supporting
confidence: 92%
“…Biofertilizers are microbial inoculants which are capable in nitrogen fixation, phosphorus solubilising and decomposing organic matter at a faster rate and thus help in improving the soil fertility and boosting crop productivity. These results confirm the findings of Sharma et al, (2017) [13] , Tiwari et al, (2018) [17] and Kumura et al, (2019) [7] in African marigold. The maximum plant spread (21.80, 27.83 and 34.94 cm 2 ) at 30, 60 and 90 days after transplanting was recorded with T7 -75% RDF + FYM + VC + Biofertilizers, followed by treatment T6-75% RDF + VC + Biofertilizers.…”
Section: Effect Of Different Organic and Inorganic Sources Of Nutrien...supporting
confidence: 92%
“…The increase in flower yield might be due to active and rapid multiplication of bacteria especially in rhizosphere creating favourable ~ 7 ~ condition for nitrogen fixation and phosphorus solubilization at higher rate through nitrogen supply by nitrogenous fertilizers and supply of bio-fertilizers which leads to the robust growth and maximum increase in flowering span, flower diameter and flower number. These findings were in accordance with the result of Yadav et al, (2018) [20] , Patel et al, (2018) [10] , Kumura et al, (2019) [7] and Chaupoo et al, (2020) [4] in African marigold. In the present investigation, significantly higher flower yield per plot was observed under the combined application of different doses of NPK and organic manures (FYM and Vermicompost) along with bio-fertilizers.…”
Section: Effect Of Different Organic and Inorganic Sources Of Nutrien...supporting
confidence: 92%
“…T 9 (75% of the recommended dose of chemical fertilizer + EM Bokashi 2.5q/ha) resulted in minimum days to male flower appearance and the maximum days were observed in T 1 . The earliness in flowering may be due to the better translocation of nutrients to the aerial parts of the plants and enhancement of the reproductive phase due to the combined effect of organic and inorganic fertilizers as compared to exclusive inorganic fertilizers [18]. The results are in line with the findings of Martinetti and Paganini [11], Ezzo et al [19], Thriveni et al [14], Vishwakarma et al [9], Anjanappa et al [20] and Singh et al [21] who observed earliness with Integrated Nutrient Management.…”
Section: Days To First Male Flower Appearancementioning
confidence: 99%